2007
DOI: 10.1007/s00204-007-0250-1
|View full text |Cite
|
Sign up to set email alerts
|

Uterotrophic assay, Hershberger assay, and subacute oral toxicity study of 4,4′-butylidenebis(2-tert-butyl-5-methylphenol) and 3-(dibutylamino)phenol, based on the OECD draft protocols

Abstract: We performed a uterotrophic assay, the Hershberger assay, and a 28-day repeated-dose toxicity study [enhanced Organization for Economic Co-operation and Development (OECD) test guideline No. 407] of 4,4'-butylidenebis(2-tert-butyl-5-methylphenol) and 3-(dibutylamino)phenol, based on the OECD draft protocols. In the uterotrophic assay of 4,4'-butylidenebis(2-tert-butyl-5-methylphenol), female SD rats were subcutaneously injected with the chemical at doses of 0, 100, 300, and 1,000 mg/kg on each of 3 days from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…For the in vivo assay, OECD Test Guideline 407, a repeated dose 28-day oral toxicity study in rodents, is a screening assay conducted to detect endocrine disrupters acting through various toxicity mechanisms. Several chemicals have been evaluated with this assay. In our study, IAA treatment increased the weights of the hypothalamus and reduced the weights of the ovaries of the female rats. The previous in vitro study reported that treatment with IAA inhibits antral follicle growth and decreases estradiol levels in mouse ovarian follicles .…”
Section: Discussionmentioning
confidence: 72%
“…For the in vivo assay, OECD Test Guideline 407, a repeated dose 28-day oral toxicity study in rodents, is a screening assay conducted to detect endocrine disrupters acting through various toxicity mechanisms. Several chemicals have been evaluated with this assay. In our study, IAA treatment increased the weights of the hypothalamus and reduced the weights of the ovaries of the female rats. The previous in vitro study reported that treatment with IAA inhibits antral follicle growth and decreases estradiol levels in mouse ovarian follicles .…”
Section: Discussionmentioning
confidence: 72%